The Effects of Synthetically Modified Natural Compounds on ABC Transporters - Daniel Dantzic; Pawan Noel; Fabrice Merien; Dong-Xu Liu; Jun Lu; Haiyong Han; Mark J. McKeage; Yan Li (Pharmaceutics, 2018)
Multidrug resistance (MDR) is a major hurdle which must be overcome to effectively treat cancer. ATP-binding cassette transporters (ABC transporters) play pivotal roles in drug absorption and disposition, and overexpression of ABC transporters has been shown to attenuate cellular/tissue drug accumulation and thus increase MDR across a variety of cancers. Overcoming MDR is one desired approach to improving the survival rate of patients. To date, a number of modulators have been identified which block the function and/or decrease the expression of ABC transporters, thereby restoring the efficacy of a range of anticancer drugs. However, clinical MDR reversal agents have thus far proven ineffective and/or toxic. The need for new, effective, well-tolerated and nontoxic compounds has led to the development of natural compounds and their derivatives to ameliorate MDR. This review evaluates whether synthetically modifying natural compounds is a viable strategy to generate potent, nontoxic, ABC transporter inhibitors which may potentially reverse MDR.